Tle distribution and diversity in metagenomic datasets reveal niche specialization - Egan, F.; Reen, F.; O'Gara, Fergal (Wiley-Blackwell, 2015)
The existence of microbial communities and the complex interactions that govern their dynamics have received considerable attention in recent years. Advances in genomic sequencing technologies have greatly enhanced our understanding of 'what is there'. However, the question as to 'what are they doing' remains less well defined. The continual development of the genomic and metagenomic sequence databases provides an exciting opportunity to interrogate the distribution and prevalence of key microbial systems across a diverse set of ecosystems. The widely distributed type VI secretion system (T6SS) has been shown to play a significant role in bacterial-bacterial and bacterial-host interactions. While several T6SS effectors have been shown to target the cell wall and membrane of competing cells, little is known about the roles these proteins play in different ecosystems. Therefore, the prevalence of a key T6SS effector superfamily known as type six lipase effectors (Tle) was studied in over 2000 metagenomic datasets representing diverse ecosystems and host niches. Increased Tle representation in environmental categories strongly supports the hypothesis of niche specialization and suggests that these effectors may play important niche-specific roles.